Antioxidant potential and LC/MS metabolic profile of anticancer fractions from Echium angustifolium Mill. aerial parts - Hanan M. El-Tantawy, Ahmed R. Hassan, Hala E. Taha (Journal of Applied Pharmaceutical Science, 2021)
Despite the fact that Echium angustifolium growing in Egypt is used for grazing and medicinal uses, as well as a previous work showed that some isolated lignans revealed strong cytotoxic activity, there is rarity of scientific data concerning the chemical and biological profiles of the plant. Accordingly, our study was conducted to complementarily investigate in vitro anticancer activity of the plant’s aerial parts supported by bioguided chromatographic fractionation of the total extract along with tentative identification of the bioactive fractions. Our results represented that the total extract inhibited the growth of HEPG2 and HCT116 cancer cell lines with IC50 = 22 ± 0.6 and 15 ± 1.1 μg/ml, respectively. Two promising subfractions (Ea-DfD and Ea-DfE) resulting from extensive fractionation possessed remarkable anticancer activities with IC50 10 ± 0.2 and 4 ± 0.5 μg/ml against HEPG2 and IC50 4 ± 0.8 and 11 ± 0.7 μg/ ml toward HCT116, respectively. Additionally, the antioxidant activity of these two active subfractions was evaluated in vitro using the 2,2′-diphenyl-1-picryl-hydrazyl hydrate, 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonate), ferric-reducing ability power, and oxygen radical absorbance capacity assays which confirmed their antioxidant potential compared to Trolox (reference drug). Furthermore, these activities could be attributed to the presence of phenolic acid derivatives and lignans in Ea-DfD and Ea-DfE that were tentatively identified using LC-ESI-MS analysis.
Keywords: Echium angustifolium, anticancer activity, antioxidant activity, phenolic acid derivatives, lignans.